THYROID-ASSOCIATED OPHTHALMOPATHY WITH SUSPECTED SECONDARY GLAUCOMA - Marie Yuni Andari (Unram Medical Journal, 2022)
Thyroid-associated ophthalmopathy (TAO) is a thyroid hormone imbalance thatmanifests in the eye. The most common TAO is in Grave’s Disease. TAO could increase theintraocular pressure and could cause a glaucoma optic neuropathy and therefore secondaryglaucoma could happen.